EFFECTIVENESS OF CYTOLOGY FOR DIFFERENTIAL DIAGNOSIS OF MALIGNANCEES OF THE STOMACH - N. ÖRMECİ and Y. UEİ and M. ITABASHI and S. YOSHIDA and K. MARUYAMA and Ö. UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-